PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PADA ABANK IRENK YOGYAKARTA - Mutamassikin Mutamassikin; Mohammad Suyanto; Armadyah Amborowati (Universitas Janabadra, 2018)
Strategic enterprise architecture planning to improve endurance using TOGAF ADM on Abank Irenk Yogyakarta with intention of designing blueprint information system and technology information. This study uses the TOGAF ADM framework with restrictions on. Architecture Vision, Businnes Architecture, Information Systems Architecture, and Technology Architecture. Abank irenk Yogyakarta has been using information system and technology information in its business process but has not been fully incorporated and still independent. Where each work unit has its own needs and tasks without any resources that can be shared. Data is still manual in distribution make often to occurs in the recording, searching and processing the data needed properly and correctly. This gap is successful Strategy to align the implementation of information system and technology information strategy to corporate strategy that required enterprise architecture that can reduce operational and development of business strategy based on information system and technology information. Modeling of functional activities using the value chain. 10 areas. 5. A customizable strategy between corporate strategy and functional architecture. Keywords: TOGAF ADM, Value Chain, Enterprise Architecture